Screening of bioactive components from traditional Chinese medicines using cell membrane chromatography coupled with mass spectrometry. Issue 4 (24th March 2018) - Han, Shengli; Lv, Yanni; Wei, Fen; Fu, Jia; Hu, Qi; Wang, Sicen
Abstract: Introduction: Cell membrane chromatography (CMC), as a highly selective type of affinity chromatography, has been demonstrated as an effective method to screen bioactive components acting on specific receptor from a complicated biological system. Objective: To review the recent research progress and the technical applications of these analytical methods using CMC combined with gas chromatography‐mass spectrometry, (GC/MS) and liquid chromatography‐mass spectrometry (LC/MS). Methodology: In this review, we briefly introduce the CMC offline GC/MS, CMC online GC/MS, CMC offline LC/MS, and CMC online LC/MS system. And the practical application of these technologies is also enumerated. Then the future of these technologies and research methods were discussed. Results: Many bioactive components interacting with specific receptors have been screened and identified in traditional Chinese medicines. Conclusion: CMC technique has been combined with GC/MS and HPLC/MS and these combined systems have been successfully used to screen bioactive components acting on specific receptors from a complicated biological system. Abstract : We briefly introduce the CMC offline GC/MS, CMC online GC/MS, CMC offline LC/MS, and CMC online LC/MS system. And the practical application of these technologies is also enumerated. The CMC technique has been combined with GC/MS and HPLC/MS and these combined systems have been successfully used to screen bioactive components acting on specific receptors from a complicated biological system.